Corporate Social Responsibility in Garment Sourcing Networks: Factory Management Perspectives on Ethical Trade in Sri Lanka - Perry, Patsy (Journal of business ethics, 2015)
With complex buyer-driven global production networks and a labour-intensive manufacturing process, the fashion industry has become a focal point for debates on the social responsibility of business. Utilising an interview methodology with influential actors from seven export garment manufacturers in Sri Lanka, we explore the situated knowledge at one nodal point of the production network. We conceptualise factory management perspectives on the implementation of corporate social responsibility (CSR) in terms of the strategic balancing of ethical considerations against the commercial pressures of cost and lead time. Factory managers framed CSR in terms of compliance, rather than going above and beyond regulatory requirements; seeing it as a strategic competitive imperative and less a developmental mechanism. Sri Lankan manufacturers maintain that they have benefitted from a unique combination of factors, including strict national labour laws, an educated workforce, the characteristics of the garments produced, industrial upgrading, and long-term non-adversarial buyer–supplier relationships, which they argue has supported the establishment and maintenance of CSR practices. The paper thus provides managerial implications that relate CSR activities to CSR outcomes which include both reputational and production benefits. Such insights will be of strategic relevance for lead retail buyers as well as apparel producers keen to invest in CSR to partly mitigate against increasing price-based competition.